Pengaruh Penerapan Metode Sorogan Dan Wetonan Terhadap Kemampuan Berfikir Kritis Santri Di Pondok Pesantren Darul Ulum Karangpawitan - Izzan, Ahmad; Oktaviani, Sofa (STAI Al-Musaddadiyah Garut, 2022)
Critical thinking is a manifestation of learning behavior, particularly in relation to problem-solving. In critical thinking, students are required to use cognitive abilities to test the effectiveness of their thinking in solving problems and addressing errors or deficiencies. As we know, the sorogan and wetonan methods are traditional methods that have persisted amidst the emergence of various modern teaching methods today. Therefore, the sorogan and wetonan teaching methods can promote critical thinking in students. The objective of this research is to describe the influence of the application of the sorogan and wetonan methods on students' critical thinking skills. This will help to understand the relationship between the application of the sorogan and wetonan methods (Variable X) and critical thinking (Variable Y). The research method used is descriptive quantitative, involving the collection of data or information about the phenomenon under study. Data collection techniques include observation, interviews, and the distribution of questionnaires to 23 respondents. Data processing is conducted through statistical data analysis. The results indicate that the sorogan and wetonan methods have an average score of 40.9, falling within the interval range above 39, classified as very high. Meanwhile, the students' critical thinking ability has an average score of 41.7, also within the interval range above 39, classified as very high. Statistical tests show a significant influence of the sorogan and wetonan methods on students' critical thinking ability, amounting to 59%, with the remaining 41% determined by other factors. Keywords: Sorogan and Wetonan Methods, Critical Thinking, Cognitive Ability, Descriptive Method.